EGFP transgene: a useful tool to track transplanted bone marrow mononuclear cell contribution to peripheral remyelination - Piñero, Gonzalo Miguel (2018)
Bone marrow mononuclear cells (BMMC) constitute a heterogeneous population with potential to promote tissue regeneration. For this reason, this cell fraction has recently become a therapeutic alternative to mesenchymal stem cells, as culture is not required and phenotypic transformations can be hence avoided. In this work, and in order to attain long-lasting cell labeling and study longer survival times, we used BMMC isolated from adult transgenic rats expressing GFP to reproduce our wild type model and evaluate their remyelination ability in a reversible model of Wallerian degeneration. RT-PCR and flow cytometry analysis confirmed that cells isolated from the transgenic strain exhibited similar expression levels of markers specific to multipotent progenitors (CD34, CD90 and CD105) and Schwann cells (MPZ, MBP, S100β and p75NTR) compared to wild type BMMC. BMMC expressing GFP retained their migration capacity, arriving exclusively at the injured nerve. Most importantly, and as detected through long-lasting cell tracking, some of these BMMC settled in the demyelinated area, mingled with endogenous cells, underwent phenotypic changes and colocalized with Schwann cell markers MBP and S100β. Also worth highlighting, transgenic BMMC replicated wild type BMMC effects in terms of MBP organization and levels. On the basis of these findings, BMMC isolated from transgenic animals constitute a useful tool to evaluate their role in peripheral nervous system demyelination-remyelination and the underlying mechanisms.